Effect of Oral Insulin on the Severity and Recovery of Methotrexate-Induced Gastrointestinal Mucositis in the Rat. Issue 2 (February 2017) - Kuiken, Nicoline S.S.; Rings, Edmond H.H.M.; Havinga, Rick; van der Aa, Stijn A.J.; Groen, Albert K.; Tissing, Wim J.E.
ABSTRACT: Objectives: Gastrointestinal (GI) mucositis is an adverse-effect of chemo- and radiotherapy. Oral insulin has been suggested as possible intestinal growth factor and possible intervention for GI mucositis. We aimed to determine the effect of oral insulin on the severity and recovery of mucositis in a methotrexate (MTX)-induced GI mucositis rat model. Methods: Male Wistar rats (n = 24) received a single injection of 60 mg/kg MTX intravenously at day 0. From day −3 oral insulin was added to the drinking water. Group MTX received normal drinking water, group MTX+INS0.5 received 0.5 U/mL insulin, and group MTX+INS1 received 1 U/mL insulin in drinking water. The severity of mucositis was determined by intake, bodyweight, illness, and plasma citrulline. In the recovery phase, the function of the gut was tested with an oral glucose tolerance test, and villus and crypt length of the small intestine were measured. Results: MTX-induced mucositis in all 3 groups and oral insulin did not cause a change in the severity of mucositis, with comparable bodyweight, food intake, and water intake. Oral insulin did not alter the enterocyte mass, determined with plasma citrulline. The glucose level after bolus was higher in the MTX group than the MTX+INS1 group ( P < 0.05). Histology was not significant different between all groups. Conclusions: Oral insulin does not alter the severity or the acceleration of recovery of mucositis. Therefore, we conclude that it is not useful to further study oral insulin as possible intervention to prevent or treat chemotherapy-induced GI mucositis. Abstract : Supplemental Digital Content is available in the text